ANALISIS TINGKAT PENDAPATAN PETANI GARAM KAWASAN PESISIR DI KABUPATEN REMBANG - Aisyah Mirandi; Ida Nuraini; M.Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2019)
This study aims to analyze the effect of variable land area, labor, working capital and selling prices on the income level of salt farmers in Rembang Regency. In this research using primary data through the distribution of questionnaires and direct interviews with 45 respondents of salt farmers as farmers who are owners in Rembang Regency, with a list of questions prepared. The analytical method used is multiple linear regrei, classic assumption test: normality, multicollinearity and heteroscedacity, hypothesis testing : T statistical test, F statistical test and coefficient of determination. The results of this study indicate that the variable area of land, labor and selling prices have a significant positive effect on the income of salt farmers, while for the working capital variable has a positive but not significant effect on the income of salt farmers